Pelatihan Pajak UMKM Bagi Masyarakat Migran Indonesia Di Malaysia - Venusita, Lintang; Pujiono, Pujiono; Aisyaturrahmi, Aisyaturrahmi; Nuswantara, Dian Anita (Abimanyu: Journal of Community Engagement, 2025)
Compliance with laws and regulations is one of the obligations for MSMEs, but unfortunately this has not been fulfilled by MSME actors. On the other hand, taxes are the main part of government funding that is needed for sustainable development. The increase in income earned by MSME actors requires an increased understanding of taxes. The income earned by MSME actors will be taxed if it has reached the limit of provisions in accordance with applicable tax regulations. Therefore, it is deemed necessary for Indonesian migrant workers (PMI) as prospective MSME actors in general to obtain adequate knowledge related to tax aspects. This is so that there are no errors in calculations, payments and reporting in the aspect of taxation. With an in-depth knowledge of taxation for prospective MSME actors, it will help the state in optimizing tax revenue. Therefore, it is expected for prospective MSME actors to master aspects of taxation. Keywords: MSME, Tax, Indonesian migrant worker